Cartographie de l’érosion hydrique des sols et priorisation des mesures de conservation dans le territoire d’Uvira (République démocratique du Congo) - Jean Nacishali Nteranya (VertigO, 2021)
Soil erosion is among the natural hazards that are exacerbated by human activities in the Democratic Republic of Congo (DRC). However, there is little information on the spatialization of this phenomenon at the territorial level in the DRC. This study assesses the potential use of Geographic Information System (GIS) techniques and open access data to map areas at risk of erosion and prioritize areas for soil conservation in Uvira’s territory. In terms of results, 52.79% of this territory is characterized by a low risk of erosion with an average soil loss of 6.08 t ha-1 year-1 while 47.21% faces a risk of soil loss which excess the tolerable limit of 11 t ha-1 year-1 for highlands of tropical areas. This risk is accentuated by the loss of vegetation cover in profit of agricultural activities and urbanization. The low level of sensibility to erosion is found in the Ruzizi plain while the areas in the plateaus are highly susceptible due to their rugged terrain and high rainfall intensity. The statistical analysis of the frequency ratios of landslide shows the existence of a relationship between their occurrence and erosion intensity zones defined on the basis of the Universal Soil Loss Equation (USLE model). Soil loss modeling for different soil protection methods shows that the grassland banding and terracing approach are most appropriate to reduce the risk of erosion in this area. These methods can be combined with afforestation efforts for effective soil protection in Uvira.